2016
DOI: 10.1111/jvs.12369
|View full text |Cite
|
Sign up to set email alerts
|

A common lack of demographic equilibrium among tree species in Białowieża National Park (NE Poland): evidence from long‐term plots

Abstract: Questions: Does the size structure characterizing particular tree species in natural forest stands converge towards a steady state? What is the main reason for departures of observed tree size distributions from equilibrium models? What is the consequence of long-term strict protection for the demography of tree species and the conservation of associated biota?Location: Stands of natural forest in Białowie_ za National Park (NE Poland) that have been under strict protection for about 90 yr.Methods: Data on rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
102
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(108 citation statements)
references
References 31 publications
3
102
2
1
Order By: Relevance
“…Whilst analysing the growth and development of stands at permanent experimental plots, they found that some of the so-called primeval species, such as oak, pine, ash and aspen, are now ageing populations, threatened by an at least temporary disappearance from the stand layer. The most expansive species in areas under strict protection proved to be hornbeam and lime (Brzeziecki et al 2012;Brzeziecki et al 2016). The authors also pointed out that the likely loss of some forest tree species in the stand will result in a decrease of the overall diversity of the forest ecosystems in Białowieża Forest.…”
Section: Species Diversity Of the Standsmentioning
confidence: 99%
See 3 more Smart Citations
“…Whilst analysing the growth and development of stands at permanent experimental plots, they found that some of the so-called primeval species, such as oak, pine, ash and aspen, are now ageing populations, threatened by an at least temporary disappearance from the stand layer. The most expansive species in areas under strict protection proved to be hornbeam and lime (Brzeziecki et al 2012;Brzeziecki et al 2016). The authors also pointed out that the likely loss of some forest tree species in the stand will result in a decrease of the overall diversity of the forest ecosystems in Białowieża Forest.…”
Section: Species Diversity Of the Standsmentioning
confidence: 99%
“…As a heliophilous species, it is not finding favourable regeneration sites under the dense canopy of hornbeam. Interesting research spanning several decades on the variability of species composition in the protected forests of Białowieża National Park (BNP) is presented by Bernadzki et al (1998), Brzeziecki et al (2012) and Brzeziecki et al (2016). Whilst analysing the growth and development of stands at permanent experimental plots, they found that some of the so-called primeval species, such as oak, pine, ash and aspen, are now ageing populations, threatened by an at least temporary disappearance from the stand layer.…”
Section: Species Diversity Of the Standsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many forest studies, especially long-term ones, describing the dynamics of forest ecosystems found outside of direct human influence, may contain valuable guidelines that can be used to protect forests with unique characteristics (e.g. Andrzejczyk, Brzeziecki 1995, Bernadzki et al Bielak 2009Drozdowski et al 2010;Brzeziecki et al 2016;Brzeziecki et al 2017). Some of the foresters' antagonists are clearly fearful that foresters will start looking at the trees of the Forest through the prism of the raw wood that can be obtained and sold, which would undoubtedly threaten the Forest's sustainability.…”
Section: Introductionmentioning
confidence: 99%